2016
DOI: 10.1063/1.4946877
|View full text |Cite
|
Sign up to set email alerts
|

Development of a reaction cell for in-situ/operando studies of surface of a catalyst under a reaction condition and during catalysis

Abstract: Tracking surface chemistry of a catalyst during catalysis is significant for fundamental understanding of catalytic performance of the catalyst since it allows for establishing an intrinsic correlation between surface chemistry of a catalyst at its working status and its corresponding catalytic performance. Ambient pressure X-ray photoelectron spectroscopy can be used for in-situ studies of surfaces of different materials or devices in a gas. To simulate the gaseous environment of a catalyst in a fixed-bed a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 20 publications
1
64
0
Order By: Relevance
“…With regard to the OCM selectivity,t he active site has been extensively discussed for Mn/Na 2 WO 4 /SiO 2 (or supported on other oxides). [1,2,9,11,14] In our previous study, [1d] we confirmed that Mn and Ware not essential components for the selective OCM reaction. However, H 2 Owas identified as ak ey reactant (wet condition).…”
Section: Angewandte Chemiesupporting
confidence: 77%
See 1 more Smart Citation
“…With regard to the OCM selectivity,t he active site has been extensively discussed for Mn/Na 2 WO 4 /SiO 2 (or supported on other oxides). [1,2,9,11,14] In our previous study, [1d] we confirmed that Mn and Ware not essential components for the selective OCM reaction. However, H 2 Owas identified as ak ey reactant (wet condition).…”
Section: Angewandte Chemiesupporting
confidence: 77%
“…Thes urface states of the Na 2 WO 4 /TiO 2 catalyst under different gas atmospheres (O 2 + H 2 Oo rO 2 + CH 4 )a t8 00 8 8C were investigated using the AP-XPS system using af lowing reaction cell built by the Taogroup. [9] Photoemission features of subshell electrons of surface atoms can be collected when the catalyst is heated up to 850 8 8Cinaflowing gas.The Na 1s, O1s, and W4ffeatures of the catalyst in UHV and different gas atmospheres at different temperatures are shown in Figure 3. Theb inding energies of these spectra were calibrated to Au 4f 7/2 of Au foil, which was used to support the Na 2 WO 4 /TiO 2 catalyst particles (Supporting Information, Figure S7).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[23,24] Althoughahigh-pressure cell method( HPCM) can be exploited, there still exists ag ap between the in operando species(at high pressures andtemperatures) and the in situ results (after gas evacuation and cooling, HPCM) because the in operando speciesmay evolve in the evacuation or cooling processes. [11,18,19,27,28] In this work, we reporta ni noperando study under near-ambient pressure to give detailedi nsights into the CO 2 hydrogenation on the Cu(111)s urface by using NAP-XPS. [11,18,19,27,28] In this work, we reporta ni noperando study under near-ambient pressure to give detailedi nsights into the CO 2 hydrogenation on the Cu(111)s urface by using NAP-XPS.…”
Section: Introductionmentioning
confidence: 99%
“…The surface states of the Na 2 WO 4 /TiO 2 catalyst under different gas atmospheres (O 2 +H 2 O or O 2 +CH 4 ) at 800 °C were investigated using the AP‐XPS system using a flowing reaction cell built by the Tao group 9. Photoemission features of subshell electrons of surface atoms can be collected when the catalyst is heated up to 850 °C in a flowing gas.…”
mentioning
confidence: 99%
“…With regard to the OCM selectivity, the active site has been extensively discussed for Mn/Na 2 WO 4 /SiO 2 (or supported on other oxides) 1, 2, 9, 11, 14. In our previous study,1d we confirmed that Mn and W are not essential components for the selective OCM reaction.…”
mentioning
confidence: 99%